The TAPS project. 16: Difficult to place, long term psychiatric patients: risk factors for failure to resettle long stay patients in community facilities. Issue 6860 (24th October 1992) - Dayson, D.; Gooch, C.; Thornicroft, G.
Abstract : OBJECTIVE–To identify patients who could not be resettled in the community as part of the closure plans of two psychiatric hospitals and to determine their numbers and risk factors for failure. DESIGN AND SETTING–Prospective study of the closure of Friern and Claybury psychiatric hospitals. PATIENTS–The first third (369) of long stay psychiatric patients to be resettled. OUTCOME MEASURES–Reasons for patients being readmitted to hospital and not leaving the patients' service needs. RESULTS–22–6% of both hospitals' long stay patients–were not successfully resettled in the community. Eighteen continuing care places per 100, 000 of catchment area population seem to be required for this group. Patients whose placements were unsuccessful were usually readmitted because of a deterioration of their mental state and aggressive behaviour, both of which persisted and necessitated their continuing stay in hospital, often in a locked ward. Risk factors associated with failure were a high level of psychosis; a diagnosis of paranoid psychosis; incontinence; and being male. But having a social network, especially a large one, seemed to aid successful placement in the community. CONCLUSION–Rehabilitation efforts should be focused on the characteristics of these patients that put them at risk of failing to succeed in community placements.